Insensible and Inexplicable - On the Two Meanings of Occult - Florian Sprenger (communication +1, 2015)
While the distinction between spiritualism and science was understood affirmatively as a demarcation of true science against pseudo-science, nowadays, after several Science Wars, it is obvious for us that this distinction does not correspond to the actual practices of science but reflects a work of ‘purification’ typical for modernity in the Latourian sense. In the physico-philosophical surroundings of this boundary epistemological foundations are shaped and modern science is constituted as the primary way to knowledge. Referring to studies on the history of the occult in the early modern period, the article shows that in order to understand the stakes of spiritualism and its technical or personal media we should trace back this boundary to a rarely recognized conceptual transformation of the ‘occult’. It shifts between insensible and inexplicable. Following this leading difference, the article traces its function in the emergence of early occultism, the debate between Leibniz and Newton, and the rise of modern spiritualism and its instrumental repertoire.